Enhanced control strategies of VSG for EV charging station under a low inertia microgrid. Issue 13 (1st October 2020) - Rasool, Aazim; Yan, Xiangwu; Rasool, Urfa; Abbas, Farukh; Numan, Muhammad; Rasool, Haaris; Jamil, Mohsin
Abstract : The droop control strategies can realise an autonomous power allocation among virtual synchronous generators (VSGs) that can provide the recompenses of reduced system complexity and enhanced reliability. The stability of a low‐inertia microgrid can be improved by implementing a VSG, designed for the coordination between multiple variable electric vehicle (EV) based charging loads. This study mainly investigates two control schemes. Firstly, the instantaneous contribution from EV charging control for any disturbance that can provide adequate damping and inertia to a low‐inertia microgrid without degradation of the battery. Secondly, the adjustment of Q – V droop control is suggested by correcting the excitation voltage of a VSG. This method can reduce the influence of line impedances and power ratings on reactive power sharing in a multi‐VSGs system. Additionally, four different active and reactive power control modes of VSG are discussed to emphasise EV charging and discharging control through the VSG controller. These modes are explained through circuit and vector diagrams in direct and quadratic coordinates. The efficacy of the proposed strategies and their influence on power sharing is theoretically demonstrated and analysed. Finally, the theoretical results are validated through extensive simulation and experimental verification.